Protocol of a retrospective, multicentre observational study on hyperthermic intrathoracic chemotherapy in Germany. Issue 7 (20th July 2020) - Markowiak, Till; Koller, Michael; Zeman, Florian; Huppertz, Gunnar; Hofmann, Hans-Stefan; Ried, Michael
Abstract : Introduction: Objective of the 'German hyperthermic intrathoracic chemotherapy (HITOC) study' is to evaluate the HITOC as additional treatment after surgical cytoreduction for malignant pleural tumours. Even though HITOC is applied with increasing frequency, there is no standardised therapy protocol concerning the technique of HITOC, the selection as well as dosage of chemotherapeutic agents and perioperative management in order to provide a safe and comparable, standardised treatment regime. Methods and analysis: This trial is a retrospective, multicentre observational study, which is funded by the German Research Foundation. Approximately 300 patients will be included. Four departments of thoracic surgery, which are performing the most HITOC procedures in Germany, are contributing to this study: Center for Thoracic Surgery at the University Hospital Regensburg, Thoracic Clinic Heidelberg of the University of Heidelberg, Center for Thoracic Surgery of the Hospital University of Munich and the Department of Thoracic Surgery at the University Hospital Freiburg. All patients who underwent surgical cytoreduction and subsequent HITOC at one of the four centres between starting the HITOC programme in 2008 and December 2019 will be included. Information on the performed HITOC will be obtained, focusing on the technique as well as the applied perfusion solution including the chemotherapeutic agent. Furthermore, parameters of the patient's postoperative recovery will be analysed to determine 30-day morbidity and mortality. Ethics and dissemination: The approvals by the local ethics committee of the respective clinic and the three participating clinics have been obtained. The results will be presented in conferences and published in a peer-reviewed journal. Trial registration number: German Clinical Trials Registry (DRKS00015012; Pre-results).